Impacto da exacerbação da Doença Pulmonar Obstrutiva Crônica nos sintomas de ansiedade, depressão, nível de atividade física e dispneia nas atividades de vida diária - Sentanin, Anna Claudia (2015)
Chronic Obstructive Pulmonary Disease is characterized by chronic airflow limitation in the lungs, dynamic hyperinflation, lung function deterioration and systemic manifestations. The worsening of the disease causes patients to insert into a cycle of inactivity, intolerance to exercise and progressive reduction of physical activity level (PAL) and ability to perform activities of daily living (ADL). Patients with COPD also experience exacerbations, which contributes to a worsening and progression of symptoms. Stable and post-exacerbated patients present psychosocial symptoms, such as anxiety and depression, which intensifies the cycle of physical activity level impairment. Therefore, the aim of this study was to compare anxiety and depression symptoms, PAL and dyspnea on ADL and verify the association between them in stable and postexacerbated patients. A cross-sectional study was conducted, which evaluated 13 patients in Post-Exacerbation Group (PEG) (68.9±9.5 years e FEV1= 50.5±18.7 % of the predicted value) and 27 patients in Stable Group (SG) (66.5±7.4 years and FEV1= 48.5±15.4 % of the predicted value). Hospital Anxiety and Depression Scale (HADS), London Chest Activity Daily Living (LCADL) and six-minute walk test (6MWT) were applied. During seven days, PAL was measured using a Yamax Digi- Walker SW-700 pedometer (Yamax, Tokyo, Japan) positioned at the patients‟ waistline; moreover, the patients responded to the International Physical Activity Questionnaire (IPAQ), short version. Shapiro-Wilk test were performed to verify the normality of the data. To verify the difference between groups, we used Student test or Mann-Whitney test and Chi- Square test was performed to verify the difference between nominal variables. For correlation analysis were performed Spearman´s and Person´s correlation. PEG patients had more anxiety symptoms (p<0.01), dyspnea on ADL (p=0.02) and lower steps on weekends (p=0,02). There were no correlations between anxiety and depression symptoms with PAH. In PEG, symptoms had a moderate correlation with dyspnea on ADL (r=0.67, p=0.01). In SG, symptoms had a moderate correlation with dyspnea on ADL (HADS-A: r=0.46, p=0.02; HADS-D: r=0.44, p=0.01). Thus, the authors concluded that post exacerbated patients are more anxious, presented lower PAH and more dyspnea on ADL compared with stable patients. Furthermore, dyspnea on ADL is associated with anxiety only in post-exacerbated patients and depression is associated with dyspnea on ADL in both groups.